Exercise to Prevent Anthracycline-Based Cardiotoxicity (EXACT): A Feasibility Study. Issue 3 (28th June 2021) - Heinze-Milne, Stefan D.; Keats, Melanie R.; Blanchard, Chris; Giacomantonio, Nicholas; MacDonald, David; Rajda, Miroslaw; Younis, Tallal; Grandy, Scott A.
ABSTRACT: This study aimed to determine the feasibility and potential efficacy of a 12-wk aerobic exercise intervention to mitigate cardiotoxicity in those with breast and hematological cancer receiving anthracycline (AC) treatment. Individuals with breast or hematological cancer that were within 8 wk of initiating AC treatment attended a 12-wk biweekly exercise program. Participants performed aerobic exercise (35%–85% heart rate reserve) on treadmills for 20–45 min per session under the supervision of research staff. Feasibility was evaluated through participant accrual and retention, program adherence, and safety. Aerobic fitness, physical activity, quality of life, and fatigue were assessed along with AC-related serum cytokines (interleukin-1β, interleukin-6, tumor necrosis factor-α, and VEGF) to explore intervention efficacy. Over 12 months, 169 participants (115 breast cancer, 54 hematological) were screened for eligibility. Forty-nine were eligible (28 breast and 21 hematological) and 15 consented (31% accrual). Ten participants completed the study and five withdrew (67% retention). Average exercise session adherence was 73% with no exercise-related adverse events. Cardiopulmonary fitness, physical activity levels, quality of life, fatigue, and serum cytokines did not change over the course of the intervention. Participant accrual and retention, program adherence, and safety statistics in this trial were within the range of similar exercise trials involving individuals with cancer. Study findings showed no postintervention change in measures of quality of life, aerobic fitness, and inflammatory cytokines, suggesting that exercise may mitigate detrimental changes in these parameters while on AC. Overall, the exercise program was feasible, and the results warrant further investigation using a randomized controlled trial approach to investigate whether aerobic exercise therapy can mitigate cardiotoxicity and improve related health and fitness outcomes for individuals receiving AC treatment.